2022
DOI: 10.3389/fonc.2022.1015308
|View full text |Cite
|
Sign up to set email alerts
|

High tumor mutation burden indicates better prognosis in colorectal cancer patients with KRAS mutations

Abstract: ObjectiveColorectal cancer (CRC) is a common type of malignant tumor of the digestive tract. Tumor mutation burden (TMB) is a potential prognostic indicator of numerous malignant tumors. This study investigated the prognostic value of TMB in CRC.MethodsThis study analyzed the clinical and somatic mutation data of patients with CRC from the Memorial Sloan Kettering Cancer Center (MSKCC) and The Cancer Genome Atlas (TCGA) cohorts. The genetic landscape was visualized using the maftools package in R software. Sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 44 publications
0
8
1
Order By: Relevance
“…Most evidence indicated that TMB could be used to evaluate the predictive prognosis [ 20 , 21 ]. In the study, we analyzed the relationship of TMB with the somatic mutation landscape in the EC and ICI scores, but the result showed that the TMB showed no significant differences between the two groups ( Figure 3(a) ).…”
Section: Resultsmentioning
confidence: 99%
“…Most evidence indicated that TMB could be used to evaluate the predictive prognosis [ 20 , 21 ]. In the study, we analyzed the relationship of TMB with the somatic mutation landscape in the EC and ICI scores, but the result showed that the TMB showed no significant differences between the two groups ( Figure 3(a) ).…”
Section: Resultsmentioning
confidence: 99%
“…As displayed in a previous study, APC mutation was related to immune evasion in CRC [ 69 ], which was consistent with the favorable immunotherapy response in the low-score group. Furthermore, SYNE1 mutation has been linked to shorter overall survival in CRC patients with liver metastasis [ 70 ], and APC mutation exhibited longer overall survival [ 71 ]. These could be reasonable explanations for the poorer prognosis in the high-score group and the better prognosis in the low-score group.…”
Section: Discussionmentioning
confidence: 99%
“…In bladder cancer, a higher TMB indicates a longer survival time 22 . Wang et al noted that a high tumor mutation burden indicates a better prognosis in CRC patients with KRAS mutations 23 . The influence of TMB on the prognosis of patients differs among different types of tumors.…”
Section: Discussionmentioning
confidence: 99%